Efeitos da deficiência de tiamina sobre aspectos cognitivos espaciais e perfil do proteoma talâmico de ratos wistar - Polliana Toledo Nunes (2016)
Acute thiamine deficiency (TD) results in progressive neurological changes, which if left untreated, can lead to chronic brain damage and cognitive deficits, featuring a class of neurodegenerative diseases, called nutritional neurodegenerative diseases. Studies using rodent TD experimental model have shown that TD causes neurochemical changes and injuries in different regions of the Central Nervous System (CNS) and cognitive and motor impairment, which are similar to the deficiencies observed in humans. The involvement of specific proteins in the molecular mechanisms responsible for the neuronal death that leads to cognitive changes has been investigated by several groups, including our own. In previous studies, our group has shown that TD alters regulation of a protein present in the synaptic vesicle, synapsin I, and affects certain proteins levels in the thalamus. Among the proteins affected, the voltage-dependent anion channel (VDAC) was identified, an important protein for cell maintenance and survival. In addition, we verified that these effects are associated with spatial cognitive performance of the rats. According to these results, we decided to perform a more detailed and extensive study. The aim of the present study was to investigate the proteomic profile of the thalamus of male Wistar rats thiamine deficient. In addition, the spatial cognitive performance, learning and memory were assessed, using the Morris Water Maze task (MWM). We used the pyrithiamine-induced thiamine deficiency model in adult rats (PTD). After the onset of the last neurological signs, the TD was interrupted. Following two weeks of recovery, spatial cognitive tasks using the MWM were performed. One day after the behavioral test, the animals were killed and the thalamus were dissected. We observed that TD affects the body weight gain, and food and water intake. In addition, we noted that the PTD animals showed deficits in performance during the learning process, which was reverted by training. The neuroproteomic analysis, using label-free quantification, revealed deregulation of 183 proteins, out of 1440 proteins identified. Among these 183 proteins, 153 were down-regulated and the remaining were up-regulated after the vitamin deficiency. Using bioinformatics tools, the proteins were categorized and associated according to functional annotation and signaling, and to metabolic pathways. These analyses showed that the TD affected proteins involved in different biological processes, cellular components and molecular functions. One of the biological processes affected was oxidative stress mechanism, which is involved in the TD neurodegeneration process. Seven of the proteins identified in the proteomic analysis were involved in this mechanism and were altered in comparison to the control animals. Other evidence relating oxidative stress mechanism dysregulation to TD is the alteration of a protein known as ferritin, which is considered a marker of cells exposed to oxidative stress. Also, the pro-inflammatory cytokine up-regulated by TD indicates a possible defense mechanism in response to this process. The data also showed that the TD affects several proteins involved in the synaptic vesicle (SV) cycle function, such as complexin 2, dynamin 3, AP2 adaptor complex, V-ATPase. These down-regulations might interfere in processes such as exocytosis, endocytosis and filling of the VS and, consequently, affect the release of neurotransmitters. In addition, the synthesis of neurotransmitters can also be affected by TD, due to down-regulation of thiamine-nondependent enzymes. These enzymes are important for the maintenance of the metabolic pathways in the thalamus by TD. A modification of the balance between functional dependent system of GABA and glutamate may be a possible explanation for the recovery of information learned after repetitions of tasks. The data obtained in the present work indicates that different molecular targets that affect different pathways can be explored in further studies. These findings contribute to understanding the role of different proteins and molecular components in neurodegenerative processes that will lead to impairment of cognitive aspects.